2023
DOI: 10.3389/fphar.2023.1101036
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric and visualization analysis of kidney repair associated with acute kidney injury from 2002 to 2022

Abstract: Background: Renal repair is closely related to the prognosis of acute kidney injury (AKI) and has attracted increasing attention in the research field. However, there is a lack of a comprehensive bibliometric analysis in this research area. This study aims at exploring the current status and hotspots of renal repair research in AKI from the perspective of bibliometrics.Methods: Studies published between 2002 and 2022 related to kidney repair after AKI were collected from Web of Science core collection (WoSCC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…Besides, CHF was shown to exert renal protective effects and inhibit fibrosis by reducing TGF-β1 and CTGF [ 5 ]. Our recently published data [ 56 ] on Rhizoma Chuanxiong and Radix et Rhizoma Rhei (rhubarb) against AKI and renal fibrosis based on network pharmacology and experimental validation demonstrated that this herbal pair might inhibit tubular epithelial cell apoptosis and improve AKI and renal fibrosis by inhibiting the p38-MAPK/p53 signaling. The triglyceride metabolic pathway and fat digestion and absorption metabolic pathway discovered in this study might become new targets for CHF-II to treat A on C, and specific research strategies will be established for the next study.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, CHF was shown to exert renal protective effects and inhibit fibrosis by reducing TGF-β1 and CTGF [ 5 ]. Our recently published data [ 56 ] on Rhizoma Chuanxiong and Radix et Rhizoma Rhei (rhubarb) against AKI and renal fibrosis based on network pharmacology and experimental validation demonstrated that this herbal pair might inhibit tubular epithelial cell apoptosis and improve AKI and renal fibrosis by inhibiting the p38-MAPK/p53 signaling. The triglyceride metabolic pathway and fat digestion and absorption metabolic pathway discovered in this study might become new targets for CHF-II to treat A on C, and specific research strategies will be established for the next study.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, our study focused solely on the SCI-Expanded in WoSCC database, which may have potentially excluded relevant studies, although WoSCC database is the most commonly used database in bibliometrics. [102][103][104][105] Secondly, some high-quality studies published recently may have been underestimated in our analysis due to their limited citation frequency. Finally, due to the constantly updating nature of databases, the dataset for this year is still incomplete and therefore not included in this study.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…65 However, even so, this study still has certain limitations. Firstly, the literature data included in this study only came from the SCI-Expanded database in the WoSCC database, which is commonly used in bibliometric research, [66][67][68] and the types and languages of literature were restricted, which may result in the omission of some literature that meets the inclusion criteria. But such operations can include more high-quality research while ensuring a sufficient amount of research data to ensure the quality of this study.…”
Section: Strengths and Limitationsmentioning
confidence: 99%